Radiation unlocks the therapeutic potential of immune checkpoint blockers in lung cancer patients. (3rd August 2019) - Ko, Eric C.; Galluzzi, Lorenzo
ABSTRACT: CTLA4 blockers have limited activity in patients with chemorefractory lung cancer. Recent clinical data demonstrate that radiation therapy combined with CTLA4 blockers enables disease control in a sizeable fraction of these patients, correlating with increased circulating levels of type I interferon and dynamic changes in the peripheral T cell repertoire.